An algoritm for solving electromagnetic field equations by finite element method (2007)
Describing the behaviour of electromagnetic frequency responses from vertically inhomogenous and anisotropic earth of 2-Dimensional structures energized finite sources is computationally laborious. Differential equations were derived and their numerical solutions also sought for the desired components of electric and magnetic fields. Also, expressions for the impedance and apparent conductivity were stated. An algorithm based on the finite element method for computing approximate numerical solutions for these problems were dealinated.